INSENTIF PAJAK DALAM MERESPONS DAMPAK PANDEMI COVID-19 PADA UMKM (USAHA MIKRO KECIL MENENGAH) - Tryas Chasbiandani; Shinta Budi Astuti; Ameilia Damayanti (FEB-UP Press, 2023)
The main purpose of this study is to see the impact of the covid-19 pandemic ant the utilization of the final income tax facility borne by the government on MSMEs in Bogor Regency. The population of this study is MSMEs that receive a final income tax facility of 0,5% in PP 23/2018 which is borne by the government. The sampling technique was purposive sampling which resulted in sample of 58 SMEs in Bogor Regency. This study uses a qualitative method. This study proves that MSME actors have not fully obtained and utilized tax incentives for MSMEs due to a lack of understanding of actors related to taxation.